(untitled) (Sebha University Conference Proceedings, 2024)
The field of libraries and information has witnessed amazing technical developments that have affected all office jobs and activities. Perhaps the changes brought about by the Corona pandemic and the accompanying comprehensive closure of libraries and information centers were a stronger motivation to change the role of the information specialist in light of the digital environment and made it mandatory for him to have cognitive skills to control technologies. The services of information institutions have also turned into remote information services in order to continue work outside the workplace. This study attempts to identify the digital information services provided at the central library of Mouloud Mammeri University in the state of Tizi Ouzou in order to identify the reality of providing these services and the extent of the competence of the information specialist in presenting them for the purpose of evaluating them. These services and identifying the gaps and shortcomings in order to correct them and show the strengths to enhance them. To achieve the objectives of the study, the descriptive analytical method was used to study the reality of the situation in the central university library under study. Observation and interviews were also relied upon. Finally, the results of the study proved that the library under study is progressing. Moving forward towards digital transformation, a set of suggestions have been presented that would improve the level of information services provided, achieve the satisfaction of the audience who benefit from them, and meet their current and future desires.